El legado de Wdgar Willems a la educación musical de hoy. Herencia de Edgar Willems, pedagogo del siglo XX, a la pedagogía musical del siglo XXI (2015)
The twentieth century is considered to be that of the great educational transformation, in all areas of knowledge, in relation to knowledge processes: with a valuable legacy in pedagogical proposals based on the integral formation of the human being from its essence, allowing it to develop their abilities as being intellectual, emotional and social. Hence, the author of this paper has been allowed to consider it as the “golden age” of education and, therefore, the golden age of music education, since pedagogical and didactic proposals emerged, built on important foundations philosophical Edgar Willems was one of the main representatives of that transformative movement, whose legacy is important to know and work as a valuable heritage to the current world of music education. It is characterized by being a universal proposal, applicable to any context or musical educational environment for significant and always current contributions.